Covalent inhibitors of human papillomavirus type 16 E6 protein restore p53 function and suppress growth of HPV-driven tumors in vivo - Anne Rietz; Lokesh Kumari; Ankeeta Koirala; Stephane Pelletier; Zhijian Lu; Elliot J. Androphy (Proceedings of the National Academy of Sciences, 2026)
High-risk human papillomaviruses (HPVs) promote malignant progression through sustained expression of the viral oncoprotein E6, which drives degradation of the tumor suppressor p53 and creates an oncogenic dependency in HPV-positive cancers. Here, we identify a genotype-defined therapeutic vulnerability by selectively and irreversibly inactivating HPV-16 E6 through covalent targeting a cysteine proximal to its E6AP-binding interface. Pharmacologic inhibition of E6 restored p53 protein stability and transcriptional activity in HPV-16–positive cancer cells, inducing apoptosis and senescence while sparing HPV-negative epithelial cells. A CRISPR-engineered E6 cysteine-to-serine knock-in abolished compound activity in vitro and in vivo, establishing on-target mechanism. Transcriptomic profiling confirmed activation of p53-dependent tumor suppressor programs following E6 inactivation. In xenograft models of cervical and oropharyngeal cancer, irreversible inhibition of E6 suppressed growth of established tumors with minimal toxicity and no evidence of acquired resistance. These findings support covalent inactivation of HPV-16 E6 by a small molecule as a therapeutic strategy for HPV-associated malignancies.